Education in Making Complementary Food at Posyandu Cempaka and Edelweis, Kahuripan, Tasikmalaya - Lilik Hidayanti; Dian Saraswati; Nisatami Husnul (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
At the age of six months to two years, infant need breast milk complementary food. Mothers' ignorance about providing nutritious complementary foods can lead to low nutritional intake which ultimately results in stunted growth. This community service activity aims to increase mothers' knowledge about making breast milk complementary food through education. Participants in this activity were 70 mothers who had children under two years old in two posyandu (Cempaka and Edelweiss) at the Karuripan Community Health Center, Tasikmalaya City. The methods used in this activity include needs assessment, creating educational materials, implementing education (explaining and providing examples of how to make complementary food) and evaluation by administering pre-tests and post-tests. The results of this activity have a positive influence on increasing mothers' knowledge about making MP ASI, so that similar activities need to be carried out regularly.